2021
DOI: 10.1039/d1sc02843j
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of crystal packing in semiconducting spin-crossover materials with fractionally charged TCNQδ anions (0 < δ < 1)

Abstract: Co-crystallization of the prominent Fe(II) spin-crossover (SCO) cation, [Fe(3-bpp)2]2+ (3-bpp = 2,6-bis(pyrazol-3-yl)pyridine), with a fractionally charged TCNQδ- radical anion (0 < δ < 1) has afforded a hybrid complex [Fe(3-bpp)2](TCNQ)3·5MeCN...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…18,19,30 In some cases, for example, when TCNQ dÀ was used, additional properties such as (semi)conducting behaviour have been achieved. [31][32][33][34][35][36][37][38] However, examples of ionic SCO-cocrystals are oen highly solvated, and difficulties with reproducibility and elucidation of structureproperty correlations have been associated with desolvation effects. The use of neutral rather than charged molecules would allow the incorporation of a much wider range of coformers to be employed, increasing the modularity of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,30 In some cases, for example, when TCNQ dÀ was used, additional properties such as (semi)conducting behaviour have been achieved. [31][32][33][34][35][36][37][38] However, examples of ionic SCO-cocrystals are oen highly solvated, and difficulties with reproducibility and elucidation of structureproperty correlations have been associated with desolvation effects. The use of neutral rather than charged molecules would allow the incorporation of a much wider range of coformers to be employed, increasing the modularity of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] The conductivity of Fe(II)based SCO systems can be further enhanced by adding organic semiconducting polymers, such as polyaniline (PANI) and polar poly-D-lysine (PDL), 28,29 and select molecules. [30][31][32][33][34][35][36][37] Even interfaces can improve conductivity and mobility within adjacent SCO layers and it is likely that this also holds for valence tautomeric films.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular conductors with switchable magnetic responses hold potential for application in data processing and storage devices. In this vein, spin crossover (SCO) complexes, which show switching between high-spin (HS) and low-spin (LS) electronic configurations under changes in temperature, pressure, or photoexcitation, have been extensively investigated as switchable molecular conductors. , A most common way to achieve the combination of SCO with electrical conductivity is to cocrystallize SCO complexes with suitable organic donor or acceptor fragments, such as tetrathia­fulvalene (TTF), 7,7′,8,8′-tetracyano­quino­dimethane (TCNQ), or [M­(dmit) 2 ] n − (dmit = 4,5-dithiolato-1,3-dithiol-2-thione). For example, our group and others reported several hybrid materials that combine cationic SCO complexes with partially charged TCNQ δ− anions. , Such complexes displayed gradual temperature-induced SCO, as well as a light-induced excited spin-state trapping (LIESST) effect, and appreciable conductivity, up to 0.2 S/cm at 300 K . An intriguing approach to combining spin-state switching and conductivity in the same material was proposed by Galán-Mascarós et al, who reported SCO-induced changes in conductivity of conjugated polymers loaded with SCO nanoparticles. , …”
Section: Introductionmentioning
confidence: 99%